2011
DOI: 10.1159/000332212
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and Molecular Characterization of Y Isochromosome in a 63XO/64Xi(Yq) Mosaic Karyotype of an Intersex Horse

Abstract: Sex chromosome aberrations commonly lead to abnormal sexual development. Here we cytogenetically and molecularly characterized Y isochromosome in an intersex horse. Blood lymphocyte analysis showed a mosaic karyotype with 96% 63,XO and 4% 64,Xi(Y) cells. Molecular analysis of the isochromosome was carried out by fluorescence in situ hybridization and polymerase chain reaction with male-specific and pseudoautosomal markers from the horse Y chromosome. We found that the isochromosome was monocentric, composed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 110 publications
0
13
0
Order By: Relevance
“…1 Horse Y chromosome organization. a Cytogenetic features of the horse Y chromosome: G-band positive material corresponds to MSY (green FISH signal); C-band positive material corresponds to ETSTY7 ampliconic arrays; centromere is denoted by a red FISH signal (from published molecular profile of horse Y 68 ); b Horse MSY sequence classes and gene map; c Triangular dot-plot showing the location of 100% identical sequences in MSY (with a 100 bp motif and a 20 bp step) …”
Section: Resultsmentioning
confidence: 99%
“…1 Horse Y chromosome organization. a Cytogenetic features of the horse Y chromosome: G-band positive material corresponds to MSY (green FISH signal); C-band positive material corresponds to ETSTY7 ampliconic arrays; centromere is denoted by a red FISH signal (from published molecular profile of horse Y 68 ); b Horse MSY sequence classes and gene map; c Triangular dot-plot showing the location of 100% identical sequences in MSY (with a 100 bp motif and a 20 bp step) …”
Section: Resultsmentioning
confidence: 99%
“…However, this horse had a small penis inside the vulva and small inguinal testes, indicating an effect through a SRY gene product during development. Two other chromosomally mosaic horses with a Y isochromosome (Yq) in conjunction with a 63,X cell line were reported [Herzog et al, 1989;Das et al, 2012]. Both cases had the Y isochromosomes which were composed of 2 long arms, resulting in genetic Y disomy and overdose of PAR genes.…”
Section: Discussionmentioning
confidence: 99%
“…Pure monosomy X [Mäkinen et al, 2001;Di Meo et al, 2009;Moreno-Millán et al, 2012] and its mosaic forms [Moreno-Millán et al, 2012;Pieńkowska-Schelling et al, 2016] as well as DSD with sex reversal [Bannasch et al, 2007;Bodvarsdottir et al, 2009;Raudsepp et al, 2010;Villagómez et al, 2011;Peer et al, 2012;Anaya et al, 2014;Pieńkowska-Schelling et al, 2014] are the most common findings in mares with fertility problems [Lear and McGee, 2012]. In addition, translocations [Lear et al, 2008], trisomies [Moreno-Millán et al, 1989;Lear et al, 1999;Mäkinen et al, 1999;Brito et al, 2008], deletions [Halnan, 1985;Raudsepp et al, 2010], isochromosomes [Herzog et al, 1989;Mäkelä et al, 1994;Das et al, 2012], and copy number variations [Ghosh et al, 2014] have been reported less frequently.…”
mentioning
confidence: 99%
“…Thus, a crossover error can easily move SRY from the Y to the X The Eutherian PAR Cytogenet Genome Res 2015;147:81-94 DOI: 10.1159/000443157 91 chromosome and give rise to XX males [Ergun-Longmire et al, 2005]. However, SRY is not close to the PAB in any other eutherian species studied so far [Raudsepp et al, 2010[Raudsepp et al, , 2012Das et al, 2012], explaining why SRY -positive XX males are very rare or not found in other eutherian species [Raudsepp et al, 2010]. Therefore, a recent report about an SRY -positive 38,XX virilized tortoiseshell cat with Xp;Yp translocation [Szczerbal et al, 2015] is exceptional, particularly because the feline SRY is located 1.7 Mb proximal from the PAB [Li et al, 2013].…”
Section: The Functions Of Par Genesmentioning
confidence: 99%